2005
DOI: 10.1002/ajhb.20435
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal estimates of puberty timing in Senegalese adolescent girls

Abstract: This study aimed to assess the timing of sexual maturation (breast development and menarche occurrence) among sub-Saharan African adolescent girls from rural areas. In the framework of a longitudinal study of growth at puberty, the stages of pubertal development (Tanner classification) and menarche occurrence were recorded at intervals between 1995 and 2000 in a sample of 406 Senegalese adolescent girls from a rural area. Nutritional status was estimated during infancy, childhood, and adolescence within this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 53 publications
6
14
1
2
Order By: Relevance
“…Indeed, very slow maturation has been reported in girls from Senegal, a Sahelian country of West Africa, where adolescent girls had a median age of 16.1 years at menarche (Simondon et al 1997). This delay was later confirmed by a longitudinal study (Garnier et al 2005). Boys also presented very slow growth during pubescence (Benefice 2007).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Indeed, very slow maturation has been reported in girls from Senegal, a Sahelian country of West Africa, where adolescent girls had a median age of 16.1 years at menarche (Simondon et al 1997). This delay was later confirmed by a longitudinal study (Garnier et al 2005). Boys also presented very slow growth during pubescence (Benefice 2007).…”
Section: Introductionsupporting
confidence: 53%
“…Likewise, analysis of age at first menstruation using a national representative sample of girls confirmed that Senegalese girls menstruated later than in industrialized countries (upper limit: 12.8 years of age) (Adair and Gordon-Larsen 2001).This figure should be compared to 15.9 years (CI 95%, 15.7~16.0) currently. In addition, the onset of puberty, as assessed by breast development (B2 stage according to Tanner's classification) was 12.6 years (CI 95% : 12.5~12.8) (Garnier et al 2005). In the USA, it occurs 1.5 to 2 years earlier (Sun et al 2002).…”
Section: Slow Growth and Maturation Rates In Senegal Resulting In A "mentioning
confidence: 99%
See 1 more Smart Citation
“…La asociación de menor talla con retraso en la telarquia está en concordancia con el atraso de edad ósea y por tanto de los eventos puberales observados en niñas desnutridas 30 . En relación a estos resultados, se hace necesario el estudio de la velocidad de crecimiento entre eventos puberales, en niñas con exceso de peso y con déficit de talla, dado que pueden terminar con estaturas muy distintas influenciadas no sólo por el momento en que ocurren los eventos puberales sino por el estado nutricional con el cual se inicia esta etapa del desarrollo.…”
Section: N V E S T I G a C I ó Nunclassified
“…Few studies on pubertal onset have been conducted on African children living in Africa. [13,14] The influence of environment and geographical location on pubertal timing has been previously documented. [15,16] Most Nigerian studies have focused on age at menarche and influencing factors.…”
mentioning
confidence: 99%